Diagnostic dilemma in disseminated TB could be fatal: lesson learned through a bitter encounter - Ahmed Suparno Bahar Moni; Tiffany Ann Johnson; Cade Ray McGarvey; Razia Sultana Ivy; Tasmia Jahan Yean; Muhamad Zabidi Ahmad (The Egyptian Journal of Internal Medicine, 2023)
Abstract A definitive diagnosis of soft tissue cystic swelling is challenging, as clinical and imaging findings might misguide the clinician and delay timely diagnosis and treatment as well as outcome. The radiological features of tubercular cysts often overlap with that of sarcoma or metastatic cancer. Involvement of a multidisciplinary team, tissue biopsy, and histopathology should supplement standard diagnostic testing and imaging to confirm the diagnosis and avoid delay in treatment. We report a case of multiple cystic swelling of the upper limb, ankle, and pelvis mimicking metastatic ovarian cancer which was later diagnosed as a case of disseminated tuberculosis.